Risk of solid cancers overall and by subtypes in patients with psoriatic arthritis treated with TNF inhibitors – a Nordic cohort study. (5th January 2021) - Hellgren, Karin; Ballegaard, Christine; Delcoigne, Bénédicte; Cordtz, René; Nordström, Dan; Aaltonen, Kalle; Gudbjornsson, Bjorn; Love, Thorvardur Jon; Aarrestad Provan, Sella; Sexton, Joe; Zobbe, Kristian; Kristensen, Lars Erik; et al.
Abstract: Objectives: To investigate whether TNF inhibitors (TNFi) are associated with increased risk of solid cancer in patients with psoriatic arthritis (PsA). Methods: From the Nordic clinical rheumatology registers (CRR) here: SRQ/ARTIS (Sweden), DANBIO (Denmark), NOR-DMARD (Norway), ROB-FIN (Finland) and ICEBIO (Iceland) we identified PsA patients who started a first TNFi 2001–2017 ( n = 9655). We identified patients with PsA not treated with biologics from (i) the CRR ( n = 14 809) and (ii) the national patient registers (PR, n = 31 350). By linkage to the national cancer registers, we collected information on incident solid cancer overall and for eight cancer types. We used Cox regression to estimate hazard ratio (HR) with 95% CI of cancer (per country and pooled) in TNFi-exposed vs biologics-naïve, adjusting for age, sex, calendar period, comorbidities and disease activity. We also assessed standardized incidence ratios (SIR) in TNFi-exposed PsA vs the general population (GP). Results: We identified 296 solid cancers among the TNFi-exposed PsA patients (55 850 person-years); the pooled adjusted HR for solid cancer overall was 1.0 (0.9–1.2) for TNFi-exposed vs biologics-naïve PsA from the CRR, and 0.8 (0.7–1.0) vs biologics-naïve PsA from the PRs. There were no significantly increased risks for any of the cancer types under study. The pooled SIR of solid cancer overall in TNFi treated PsA vs GP was 1.0 (0.9–1.1). Conclusion: In this large cohort study from five Nordic countries, we found no increased risk of solid cancer in TNFi-treated PsA patients, neither for solid cancer overall nor for eight common cancer types.